Willingness to Compete: Family Matters - Almås, Ingvild; Cappelen, Alexander W.; Salvanes, Kjell G.; Sørensen, Erik Ø.; Tungodden, Bertil (Management Science, 2016)
This paper studies the role of family background in explaining differences in the willingness to compete in a cognitive task. By combining data from a lab experiment conducted with a fairly representative sample of adolescents in Norway and high-quality register data on family background, we show that family background is fundamental in two important ways. First, boys from low socioeconomic status families are less willing to compete than boys from better-off families, even when controlling for confidence, performance, risk preferences, time preferences, social preferences, and psychological traits. Second, family background is crucial for understanding the large gender difference in the willingness to compete. Girls are much less willing to compete than boys among children from better-off families, whereas we do not find any gender difference in willingness to compete among children from low socioeconomic status families. Our data suggest that the main explanation of the role of family background is that the father’s socioeconomic status is strongly associated with boys’ willingness to compete. We do not find any association between the willingness to compete for boys or girls and the mother’s socioeconomic status or other family characteristic that may potentially shape competition preferences, including parental equality and sibling rivalry. This paper was accepted by Uri Gneezy, behavioral economics.